NILAI KEARIFAN LOKAL DAN MAKNA SIMBOLIK TRADISI PENGAMBILAN DAN RUWATAN BANYU TUK 7 DESA JURANGMANGU KECAMATAN PULOSARI KABUPATEN PEMALANG - Kartono, Slamet; Harjito, Harjito (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Jurangmangu Village is the smallest village in Pulosari District, Pemalang Regency, Central Java Province, both in terms of area and population. In the 1960s, Jurangmangu experienced a golden age in the production of citrus, potatoes, and tobacco. In addition to its agricultural potential, Jurangmangu Village also has a tradition of collecting and purifying water (banyu tuk 7), which is still preserved and maintained by the Jurangmangu community. The tradition of taking and purifying Banyu Tuk 7 is a Javanese cultural practice steeped in symbolism and local wisdom. This study aims to uncover the symbolic meaning and local wisdom values ​​contained within this tradition, while also examining its relevance to modern life. In this study, the researcher employed a descriptive qualitative method. The data collection methods employed were observation, in-depth interviews, documentation, and literature review. The data collection methods used by the researcher were observation, in-depth interviews, documentation, and literature review. The data analysis method used data presentation, data reduction, and conclusion drawing. The results of the study indicate that the water fetching ritual and the purification of Banyu Tuk 7 have symbolic meaning as a means of asking for rain after a drought, as well as an expression of gratitude for the harvest and praying that Jurangmangu Village will always be blessed with blessings. In addition, this tradition contains religious, social, and cultural values ​​that remain relevant in the social, religious, and state life of the residents of Jurangmangu Village.